Implementasi Program MADINA (Maju dalam Iman dan Ilmu Anak) dalam Pembentukan Akhlak Anak Desa Kertayasa - Ayunah, Ayunah; Budi, Budi; Sri Rohmayatun (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
Students of the Muhammadiyah University of Kuningan's Community Service Program (KKN) conducted a community service activity called the MADINA Program (Advancing in Faith and Children's Knowledge) in Kertayasa Village, Panawangan District, Ciamis Regency. Through Islamic religious education implemented consistently, participatory, and contextually, this program aims to improve the formation of children's morals. Three Diniyah Takmiliyah Awaliyah (DTA) institutions served as research locations, and a qualitative approach was used to collect data through observation, interviews, and documentation. The Miles & Huberman model was used to conduct data analysis, which included presentation, verification, reduction, and drawing conclusions. The results showed that the MADINA program not only teaches the Quran, but also teaches Islamic behavior such as discipline, politeness, and what children should do in everyday life. Success in creating a religious and enjoyable learning environment depends on the active involvement of parents, DTA teachers, and the community. The MADINA program offers scientific developments in a religious community-based service model that integrates faith and character education through sustainable and participatory learning activities at the village level.